Attachment to Manga (Japanese Comics): Conceptualizing the Behavioral Components of Manga Attachment and Exploring Attachment Differences Between Avid, Moderate, and Occasional Manga Readers - Julian Pimienta (Journal of Anime and Manga Studies, 2022)
The purpose of this study is twofold. First, it seeks to conceptualize attachment to manga (Japanese comics) by extrapolating attachment theory’s behavioral markers to manga readership. Second, it compares manga attachment markers between avid, moderate, and occasional readers in order to find differences in the strength of the attachment. The study predicted that (a) attachment theory’s common behavioral markers (i.e., proximity maintenance, safe haven, secure base, and separation distress) map onto manga readership and that (b) avid readers display stronger attachment behaviors towards manga than moderate and occasional readers. Participants (N = 279) answered a questionnaire identifying a set of 24 manga attachment markers. Analyses revealed a four-component solution that mirrors attachment theory’s markers, supporting the premise that manga attachment mirrors interpersonal attachment. The results also revealed statistically significant differences in the strength of the attachment behaviors to manga between avid, moderate, and occasional readers among three behavioral markers (i.e., proximity maintenance, safe haven, and separation distress), confirming that avid manga readers maintain proximity with manga, find in manga a safe haven when feeling distressed, and experience separation distress at the real or perceived possibility of the manga not being available. These findings contribute to the increasing literature and understanding on the role of media in individual’s wellbeing.